Paulus Albarus of Muslim Cordova - Cabaniss, Allen (Church history, 1953)
In the year of the Incarnation 839, there occurred an event which alarmed the inhabitants of Frankland: a royal chaplain named Bodo, nobly born and a deacon in Holy Orders, under singularly dramatic circumstances abandoned the Christian faith for Judaism, changed his name to Eleazar, took a Jewish wife, and went to live in Saracenic Spain. The incident is remarkable for three reasons. First, it shows the vitality of Jewish proselytism in the ninth-century Western world. Secondly, it had some effect on the relations between the Frankish state and the Spanish Muslim government.